2018
DOI: 10.28998/rca.v16i1.3782
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Parameters of Black Aphid in Cowpea Cultivars

Abstract: Pode-se dizer que a sobrevivência e o desenvolvimento de Aphis craccivora Koch (Hemiptera: Aphididae) é afetado pelo tipo de planta hospedeira. Objetivou-se estimar os parâmetros demográficos do pulgão-preto (Aphis craccivora Koch) em cultivares de feijão-caupi (Vigna unguiculata (L.) Walp.) recomendadas para a colheita mecanizada no Brasil. Foram usadas as cultivares: BRS Pingo de Ouro, BRS Tumucumaque, BRS Itaim, BRS Nova Era, BRS Imponente e BRS Guariba. A cultivar VITA 7 fez parte do estudo na qualidade de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…MNCO4-792F-123 had the smallest sum of rank (Σr) value (Table 3). Thus, among the evaluated lines, MNCO4-792F-123 is the least susceptible line to the pest, using an antibiosis resistance mechanism that reduces female fecundity and increases mortality in the nymph phase (Silva et al, 2018a(Silva et al, , 2018b.…”
Section: Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…MNCO4-792F-123 had the smallest sum of rank (Σr) value (Table 3). Thus, among the evaluated lines, MNCO4-792F-123 is the least susceptible line to the pest, using an antibiosis resistance mechanism that reduces female fecundity and increases mortality in the nymph phase (Silva et al, 2018a(Silva et al, , 2018b.…”
Section: Genotypementioning
confidence: 99%
“…In Brazil, in recent years, research has been carried out to test the resistance of V. unguiculata to cowpea aphid, and to identify potential sources of resistance to it (Silva & Bleicher, 2010;Silva et al, 2012;Bandeira et al, 2015;Melville et al, 2016). There are reports on the susceptibility of several cowpea cultivars (released to the market) to cowpea aphid (Melville et al, 2016;Silva et al, 2018a). A study on the resistance to cowpea aphid in fifteen semi-erect cowpea lines, developed for the medium and large farmer, the authors observed that only two genotypes were resistant to the insect (Silva et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, são relatados poucos trabalhos referentes aos aspectos biológicos do pulgão-preto sobre o feijão-caupi (VALENTE et al, 2014;PORTELA, 2018), utilizando-se geralmente a cultivar VITA 7, pouco cultivada pelos agricultores e altamente suscetível à praga BLEICHER, 2007;SILVA et al, 2018). Por outro lado, muitas cultivares de feijão-caupi já lançadas no mercado apresentam-se como suscetíveis ao pulgão-preto (MORAES;…”
Section: Introductionunclassified
“…In Brazil, there are few studies on the biology of the cowpea aphid on cowpea (VALENTE et al, 2014;PORTELA, 2018). Those that exist generally use the VITA 7 cultivar, which is little-used agriculturally and which is highly susceptible to infestation BLEICHER, 2007;SILVA et al, 2018). On the other hand, many of the cowpea cultivars already on the market are susceptible to cowpea aphid BLEICHER, 2007;SILVA et al, 2012;BANDEIRA et al, 2015;MELVILLE et al, 2016;LOURENÇO et al, 2018;SILVA et al, 2018), This both decreases productivity and increases production costs for farmers using pest control products.…”
Section: Introductionmentioning
confidence: 99%